1999
DOI: 10.1006/dbio.1999.9216
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical Axons Are Influenced by Chemorepellent and Chemoattractant Activities Localized to Decision Points along Their Path

Abstract: Thalamocortical axons (TCAs), which originate in dorsal thalamus, project ventrally in diencephalon and then dorsolaterally in ventral telencephalon to their target, the neocortex. To elucidate potentially key decision points in TCA pathfinding and hence the possible localization of guidance cues, we used DiI-tracing to describe the initial trajectory of TCAs in mice. DiI-labeled TCAs extend ventrally on the lateral surface of ventral thalamus. Rather than continuing this trajectory onto the lateral surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 48 publications
5
104
1
Order By: Relevance
“…In retinotectal axon branching, DCC mediates the netrin-1-induced branch-promoting signal (55). Similarly, growth of TC and callosal axons at the embryonic stages is promoted by netrin-DCC signaling (56)(57)(58)(59). However, the present data show that DCC is not strongly expressed in the thalamus at P14, and its binding to NTN4 is substantially weaker than that of Unc5B (Fig.…”
Section: Discussioncontrasting
confidence: 47%
“…In retinotectal axon branching, DCC mediates the netrin-1-induced branch-promoting signal (55). Similarly, growth of TC and callosal axons at the embryonic stages is promoted by netrin-DCC signaling (56)(57)(58)(59). However, the present data show that DCC is not strongly expressed in the thalamus at P14, and its binding to NTN4 is substantially weaker than that of Unc5B (Fig.…”
Section: Discussioncontrasting
confidence: 47%
“…In contrast, in Robo2 mutants, some thalamocortical fibers were observed to fail reaching the telencephalon, and instead growing abnormally toward the ventral diencephalon, a region normally nonpermissive for thalamocortical axon outgrowth (n ϭ 4) (Fig. 4 I) (Braisted et al, 1999). DiI injections in the dorsal thalamus of control, Robo1 and Robo2 mutants confirmed that numerous thalamocortical axons failed to enter the telencephalon and instead invaded the hypothalamus in Robo2 mutants (Fig.…”
Section: Abnormal Corticospinal and Thalamocortical Projections Inmentioning
confidence: 87%
“…Several studies have examined the early development of these projections and have identified pioneering axonal populations as well as potential intermediate targets and choice points for these axons (McConnell et al, 1989;De Carlos and O'Leary, 1992;Métin and Godement, 1996;Molnár et al, 1998;Braisted et al, 1999;Tuttle et al, 1999;Auladell et al, 2000;Ló pez-Bendito et al, 2006). In addition, multiple molecules that participate in the guidance of these connections have been identified, providing a comprehensive frame in which to understand their development (Serafini et al, 1996;Métin et al, 1997;Richards et al, 1997;Braisted et al, 2000;Leighton et al, 2001;Bagri et al, 2002;Ló pez-Bendito et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, structures in the embryonic diencephalon and basal ganglia are implicated in providing signals that guide the growing axons, through attractants (Metin and Godement, 1996;Metin et al, 1997;Richards et al, 1997;Bagnard et al, 1998;Braisted et al, 1999;Braisted et al, 2000), repellents (Bagnard et al, 1998;Braisted et al, 1999;Bagri et al, 2002), or by producing pioneering axons (Mitrofanis and Guillery, 1993). In particular, groups of cells in the basal ganglia have been proposed to be intermediate targets for cortical and thalamic axons, by producing attractants or forming transient projections to the thalamus (Mitrofanis and Guillery, 1993;Metin and Godement, 1996;Tuttle et al, 1999).…”
Section: Introductionmentioning
confidence: 99%